Reflectance confocal microscopy of cutaneous melanoma. Correlation with dermoscopy and histopathology - Silvia Arroyo Rstom; Lorena Silva Libório; Francisco Macedo Paschoal (Sociedade Brasileira de Dermatologia, 2015)
Abstract In vivo Confocal Microscopy is a method for non-invasive, real-time visualization of microscopic structures and cellular details of the epidermis and dermis, which has a degree of resolution similar to that obtained with histology. We present a case of cutaneous melanoma in which diagnosis was aided by confocal microscopy examination. We also correlate the observed features with the dermoscopic and histopathological findings. Confocal microscopy proved to be an useful adjunct to dermoscopy, playing an important role as a method 'between clinical evaluation and histopathology'.